Organic photoelectric-supercapacitor power source of electric vehicle - Rahman, Mohammed Ataur; Kaw, Myo Aung; Ahmed Khan, Shaheer (The Mattingley Publishing Co., Inc., 2020)
The drawbacks of the electric vehicle are: battery pack increased weight, limited range and required additional electricity generation source to charge the batteries. The contribution of the coal plant to the production of electricity is 57% and emissions 1.4 kg / kWh, while gasoline 35% and 1.2 kg / kWh respectively. Thus, the development of an energy-boosting system for EVs is inevitable. The purpose of this study is to present a laboratory scale organic photovoltaic-supercapacitor (OPSC) power cell model as the mobile renewable energy source of electric vehicle. The laboratory scale organic photoelectric-supercapacitor (OPSC) has been developed using C-ZnO / CuO doped polymer and carbon fiber to generate electricity from solar-heat and storage. The OPSC has considered as the roof panel of EV and it has tested at a solar temperature of 300C. The test results show that the energy conversion efficiency (ηec) of 19%, voltage (Voc) 2800 mV, current density (Jsc) 522 mA/cm2, capacitance (C) 20.15 μF/cm2, energy density (Ed) 120 Wh/kg, and power density (Pd) 29 kW/kg. It would be able to reduce EV battery size by 15%, weight 7.5% and battery charging power 9%. Furthermore, the OPSC-EV roof panel would contribute to the reduction of greenhouse gas (GHG) emission 25% and help transport the population with a low level of carbonization.